Tecendo os fios das memórias de infância no processo criativo docente: um estudo com professoras de artes visuais da Casa de Cultura de Santa Maria - Freitag, Vanessa (2008)
The present master s degree thesis is related to the research line in Education and Arts of the Post Graduation Program on Education in the Federal University of Santa Maria/RS. In this sense, it had as main objective to investigate, to describe and to analyze the childhood memoirs told by three teachers of Visual Arts at the House of Culture of Santa Maria and through these, to develop the teaching creative process of them. Therefore, the methodology was characterized by a qualitative approach whose History of Topical Life was approached as a methodological line. Data were collected starting from semi-structured interviews, documental analysis and field diary as form of recording of the thoughts and of each teacher's production. About ten meetings were accomplished at the House of Culture. Then, the theoretical contribution was structured, the former, in authors that referred to the social and collective constitution of the memory (HALBWACHS, 2006; BOSI, 1994; TEDESCO, 2002, FÈLIX, 1998 and 2002; GONDAR,2005, among other) still, it was made some relationships between memory and the contemporary artistic context (KANTON, 2001; DANTO, 2006; CAUQUELIN, 2005). The latter, it was discussed on the teaching creative process as the creative process in arts, the teacher's continuous education and the influences of the personal and professional constitution in which is referred to the educational practice of them (NÓVOA, 1996; GOODSON, 1996 and 2006; OF MASI, 2003; SALLES, 1998; MARTINS, 2006, etc). Thus, in the main childhood memoirs brought by the teachers it is pointed the images and histories on family routines, the importance of the family, the lived difficulties, games, smells, tastes and flavors of the childhood that were shared with the group. The regarded teachers have graduated in a same period and because of that it was noticed similarities of experiences lived in the childhood and in their education in arts. None of them developed a creative process in art, for that, the research contributed as an incentive to the visual production as an opportunities to rethink arts methodologies and conceptions with their students.